Effective protection redux - Anderson, James E. 1943- (NBER working paper series, 1996)
This paper rehabilitates the concept of effective rate of protection for use in political economy. The usual definition corresponds to no economically interesting magnitude in general equilibrium. The effective rate of protection for a sector is redefined here as the uniform tariff which is equivalent to the actual differentiated tariff structure in its effect on rents to residual claimants in the sector. The new ERP permits a political economic ranking of across sectors, since higher uniform tariff equivalents imply higher losses of welfare sacrificed to interest groups. The new ERP converges to the old ERP under a very special set of assumption, and elsewhere generalizes the ERP concept to any economic structure in which residual claims are defined. Numerical results for the new ERP are presented for the US economy in 1982 using the USDA/ERS computable general equilibrium model. The calculated old and new ERP's are not significantly correlated.